2021
DOI: 10.1088/2515-7655/abf41a
|View full text |Cite
|
Sign up to set email alerts
|

Thermal properties of TiNiSn and VFeSb half-Heusler thermoelectrics from synchrotron x-ray powder diffraction

Abstract: Half-Heusler (HH) alloys are an important class of thermoelectric materials that combine promising performance with good engineering properties. This manuscript reports a variable temperature synchrotron x-ray diffraction study of several TiNiSn- and VFeSb-based HH alloys. A Debye model was found to capture the main trends in thermal expansion and atomic displacement parameters. The linear thermal expansion coefficient α(T) of the TiNiSn-based samples was found to be independent of alloying or presence of Cu i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…In the X IV NiSn system, the large ρ 0 could be linked to the interstitial Ni defect, which has been shown to reduce µ and cause reduced lattice thermal conductivities [26]. Minimising interstitial Ni to levels observed in the X V FeSb family (X V = Nb, Ta; < 1% Fe) [29] is likely to significantly increase the electronic performance. The temperature dependence of ρ(T) in the X IV NiSn and X V FeSb families is fundamentally different due to the larger E def in the X V FeSb materials, up to 14 eV, where n-type ZrNiSn based compositions have E def as low as 5 eV, leading to a weak temperature dependence in the latter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the X IV NiSn system, the large ρ 0 could be linked to the interstitial Ni defect, which has been shown to reduce µ and cause reduced lattice thermal conductivities [26]. Minimising interstitial Ni to levels observed in the X V FeSb family (X V = Nb, Ta; < 1% Fe) [29] is likely to significantly increase the electronic performance. The temperature dependence of ρ(T) in the X IV NiSn and X V FeSb families is fundamentally different due to the larger E def in the X V FeSb materials, up to 14 eV, where n-type ZrNiSn based compositions have E def as low as 5 eV, leading to a weak temperature dependence in the latter.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the Nb 0.8 Ti 0.2 FeSb sample shows a much stronger temperature dependence and has a much lower relative impact of ρ 0 (only ∼10% of ρ 800 K compared to ∼50% for TiNiCu 0.025 Sn). This strong temperature dependence is significant for the thermoelectric properties, with the power factor, S 2 /ρ typically decreasing with temperature in the X V FeSb system, whereas they increase in the X IV NiSn family [21,28,29]. The samples in figure 3 either have a T 1 or T 1.5 dependence of ρ(T).…”
Section: Validation Of the Model Using Temperature Resistivity Datamentioning
confidence: 97%
“…Recent work using unfolded supercell calculations has shown that new bands can emerge in substituted HH compositions (e.g. in vacancy systems, 170 for interstitials 58 and complex compositions 233 ) and this is another possible route for performance improvements. This is an area where theory could lead experiments by identifying new compositions with promising electronic bandstructures.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%
“…As indicated by defect energy calculations, inversion of X and Y is uncommon (e.g. <1% in X IV NiSn), 57 but there is evidence that this occurs for V 0.8 CoSb and VFeSb, 58,59 where V/Fe and V/Co are (almost) adjacent in the periodic table and hence likely to have similar site preferences.…”
mentioning
confidence: 99%
“…It can be inferred that off-stoichiometry in these defective compositions at low concentration is well accommodated within the sublattice implying limited yet considerable solubility of interstitials/vacancies within the HH matrix. 10,33,48,79 The refined XRD patterns corresponding to each composition are also shown in supplementary information Fig. S1-S9 with refined parameters enlisted in Table S1.…”
Section: Resultsmentioning
confidence: 99%